Giant fibroadenoma with massive infarction masquerading as malignancy: a case report - Singh, Santosh Kumar (Int Cancer Conf J, 2017)
Fibroadenoma is a common benign breast lesion that usually affects women in their second and third decade of life and usually present as small mobile painless lump. However, it is important to recognize that a small percentage have been shown to progress to giant fibroadenomas. Giant fibroadenomas can undergo infarction leading to significant morbidity and difficulty to distinguish from the more aggressive phyllodes tumors or carcinoma. We report an interesting case of giant fibroadenoma (17 × 11 × 7 cm) with massive infarction during lactation, further complicated by lactational mastitis with close resemblance to cystosarcoma phyllodes. Detailed clinical evaluation and proper investigation in the form of USG breast and PET–CT scan helped us to delineate the nature of pathology. Simple excision of lesion with curvilinear incision was done with excellent cosmetic outcome. Histopathologic features were consistent with fibroadenoma (giant) with large areas of infarction. Fibroadenoma breast has varied clinical presentations. The course of disease may be complicated by pregnancy, lactation and inflammatory processes. Massive infarction may make the picture more dubious and masquerade with malignant transformation altering our treatment decision. The presence of necrosis on core biopsy or intra-operative finding should be cautiously interpreted and is not itself a sign of malignancy. Detailed clinical evaluation and comprehensive workup should be done before embarking on radical treatment.